Propuesta para el aprovechamiento de escamas de pescado aplicado a la producción de papel de quitosano por el método de desacetilación de quitina en medio alcalino (2021)
The increase in the volumes of fishing waste in Colombia has driven this proposal to use sacles for the development of paper from chitosan, fish scales and recycled cellulose paper. The project methodology comprises three stages; In the first, the proximal composition of the Tilapia scales was determined to verify the presence of chitin, under this criterion it is defined if the sample is suitable to continue with the second phase. Next, the following critical variables for the experimental process were defined: particle size, reagent concentration, temperature and exposure time. During the second stage, two methodologies for obtaining chitosan, reported in the literature, were selected and executed. On the other hand, solubility tests were carried out in water, ethanol, acetic acid and hydrochloric acid, the flake-chitosan and chitin-chitosan yield was also calculated. Finally, the degree of deacetylation was determined through FTIR-ATR spectroscopy with a value of 84.80%, which is among the ranges reported in literature and indicates the successful production of chitosan.